2012
DOI: 10.1093/humrep/des131
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive potential of a metaphase II oocyte retrieved after ovarian stimulation: an analysis of 23 354 ICSI cycles

Abstract: BACKGROUND Live birth per cycle and live birth per embryo transfer are commonly used outcome measures for IVF treatment. In contrast, the assessment of the reproductive efficiency of human oocytes fertilized in vitro is seldom performed on an egg-to-egg basis. This approach may however gain importance owing to the increasingly widespread use of oocyte cryopreservation, as the technique is becoming more established. The aim of the current study is to quantify the reproductive efficiency of the oocyte according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 27 publications
5
40
0
1
Order By: Relevance
“…Our results are consistent with other reports pertaining to fresh embryo transfer [11, 23] that assessed the efficiency of oocyte utilization in patients aged less than 38 years according to their oocyte yield: “low,” “intermediate,” or “high.” Similar to ours, their results showed that live birth rates were equivalent in the “low,” “intermediate,” and “high” oocyte yield groups. They also reported an apparent difference in the number of oocytes required for each live birth.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with other reports pertaining to fresh embryo transfer [11, 23] that assessed the efficiency of oocyte utilization in patients aged less than 38 years according to their oocyte yield: “low,” “intermediate,” or “high.” Similar to ours, their results showed that live birth rates were equivalent in the “low,” “intermediate,” and “high” oocyte yield groups. They also reported an apparent difference in the number of oocytes required for each live birth.…”
Section: Discussionsupporting
confidence: 92%
“…However, data pertaining to the efficency, in particular live birth, of mature oocytes produced by mIVF in normal responders is understudied. Additionally, data pertaining to the assessment of reproductive efficiency based on oocyte yield of human oocytes fertilized in vitro is scarse [11]. In conventional IVF cycles, it has been reported that the oocyte utilization rate in women aged ≤ 37 years was approximately 5 % live birth per mature oocyte [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In women with ≤3 euploid blastocysts, clinical pregnancy rates were higher when a double embryo transfer was performed [14]. These findings support the hypothesis that euploid embryo cohort size is a prognosis factor in IVF treatments and that the number of euploid embryos has to be taken into account, more importantly than the percentage of euploid/aneuploid embryos, as a prognosis factor, especially if we consider cumulative pregnancy outcome [31]. In fact, according to the results of our study, both the aneuploidy and euploidy rates do not vary according to ovarian response, whereas the number of euploid and aneuploid embryos increases in the same way as number of oocytes does.…”
Section: Discussionmentioning
confidence: 62%
“…Conversely, other authors did not find negative effects of COS protocol on oocyte quality and IVF outcomes [3, 7, 39] involving other factors such as female age [46], AMH, total FSH dose, COS duration [5], or estradiol level [47]. …”
Section: Discussionmentioning
confidence: 99%